Experimental evaluation of new pipe sleeve with weep holes for concrete leakage prevention - Wan Nazri, Wan Muhammad Hafizuddin (2018)
Mortar is a layer with high water absorption rate over concrete due to its porous structure. The mortar layer that frequently exposed to water or moisture is more likely to contain moisture in its layer. The example of area that is mostly exposed to water is the bathroom. The water infiltrated and trapped in the mortar slab in the bathroom will eventually increase the moisture content of the mortar slab and will raise many problems such as the deterioration of the building structure surface. Therefore, this study has been carried out to produce a technology to remove the trapped water in the mortar slab and to reduce the moisture content in the mortar layer. The infiltration rate of the water into the mortar slabs installed with the conventional pipe sleeve (T1), the circular weep-holes pipe sleeve (T2), the vertical weep-holes pipe sleeve (T3) and the inclined weep-holes pipe sleeve (T4) have been measured and the results show that T4 has recorded the highest reading of 7.74 ml/min compared to other pipe sleeves. Besides that, T4 has also recorded the highest water flow rate out of the mortar with 1.31 ml/min and recorded the lowest moisture content of 10.1%. Inclined weep-holes pipe sleeve was proven able to work better than other designs. Therefore, the New Pipe Sleeve (NPS) performance with inclined weep-holes designs are studied in depth by changing the weep-holes angles to 15°, 30°, 45°, 60° and 75° and weep-holes surface area of 6%, 8% and 10%. As a result, the weep-holes angle of 60° with 10% weep-holes surface area has recorded the highest water infiltration rate and water flow rate out of the mortar with 20.898 ml/min and 3.764 ml/min, respectively, obtaining the highest reduction of the moisture content by 3.1%. The optimum performance of the pipe sleeve with inclined weep-holes design has been proposed by using Design Expert Software and the optimum performance can be achieved with the used of the weep-holes angle of 69.55° and 10% weep-holes surface area, producing water infiltration rate of 20.4513 ml/min and water flow rate out of the mortar of 3.3795 ml/min. Therefore, application of optimise design of weep-holes has promising potential method to reduce leakage and fungi problem that normally occurred in bathroom area.